Assessment of corneal endothelial morphology in retinal vein occlusion - Erdag, Murat; Aktas, Kasim; Canleblebici, Mehmet; Dal, Ali; Yildirim, Hakan; Balbaba, Mehmet (Bmc, 2026)
Purpose To evaluate corneal endothelial morphology in patients with retinal vein occlusion (RVO) and to investigate the differential impact of ischemic versus non-ischemic status on endothelial cell integrity, while controlling for therapeutic interventions. Methods This prospective observational study enrolled 42 patients (84 eyes) with unilateral RVO. All participants were receiving intravitreal anti-VEGF therapy as part of their standard clinical care for retinal vein occlusion-related macular edema. Based on fundus fluorescein angiography findings, participants were stratified into ischemic (n = 21) and non-ischemic (n = 21) subgroups. Detailed endothelial assessment-including endothelial cell density (ECD), average cell area, coefficient of variation (CV), and hexagonality-was performed using non-contact specular microscopy. The fellow unaffected eyes served as internal controls to calculate intra-individual differences (delta analysis), thereby minimizing the impact of inter-subject variability. The study also assessed the potential confounding roles of intravitreal anti-VEGF injections and retinal laser photocoagulation. Results Direct intergroup comparison of absolute endothelial values showed no significant differences between ischemic and non-ischemic eyes (p > 0.05). However, intra-individual analysis revealed significant subclinical endothelial compromise specific to the ischemic phenotype. Ischemic RVO eyes demonstrated a significant reduction in ECD (p = 0.010), decreased analyzable cell count (p = 0.010), and increased average cell area (p = 0.002) compared to their healthy fellow eyes. Conversely, non-ischemic RVO eyes exhibited preserved endothelial structure comparable to fellow eyes, with no significant morphometric alterations. Importantly, the frequency of anti-VEGF injections did not differ significantly between the groups (p = 0.130), suggesting that the observed endothelial changes were ischemia-driven rather than treatment-induced. Conclusion Corneal endothelial alterations in RVO are predominantly ischemia driven, whereas non-ischemic eyes maintain structural integrity. This study highlights the importance of anterior segment monitoring in ischemic RVO and support the role of ischemic burden in subclinical endothelial compromise.
Keywords: Retinal vein occlusion (RVO); Corneal endothelium; Retinal ischemia; Specular microscopy